Quran Memorization Method: A Comparative Study between Listening Method and Reading Method - Wulan Sari (Edumaspul: Jurnal Pendidikan, 2023)
The Qur'an must be memorized throughout time, beginning at the appropriate moment and ending after placing each verse. Writing down poetry, listening to them, and reading them aloud are all steps in the memorizing process. The process of memorizing will provide excellent outcomes if it is completed accurately and on schedule. Understanding the advantages of memorization and its aim can help you maintain the Qur'an in your memory. There will be a barrier to students remembering the Quran after memorization. This kind of study is qualitative research, a method that gathers data in the form of variables but sees them as a component of a whole. An analysis of the relevant literature was employed as the method for gathering data in this study. In this research, qualitative analysis was the method of data analysis. The survey's findings revealed that the memorization process used in schools was quite effective, including: 1) the school's process of seeking out teachers with teaching experience; 2) the use of memorization aids like the Qur'an, the blackboard, a memorization-friendly environment, and an adequate sound system.